Does tertiary education alleviate unemployment in middle-income countries? Insights from a dynamic panel data - Pratysto, Tangguh; Kafabih, Anim; Destiartono, Mohamad Egi (Universitas Muhammadiyah Yogyakarta, 2026)
Unemployment remains a significant issue in these middle-income countries, constraining poverty alleviation, labor productivity, and the supply of decent work amid skills mismatches and underemployment. This study examines the impact of higher education on unemployment rates in 54 middle-income countries over the period 1999–2022. This study applies the System Generalized Method of Moments (System-GMM) to dynamic panel data and controls for endogeneity and lagged effects. The controls include lagged unemployment, per capita GDP growth, CPI inflation, and government final consumption expenditure (in % of GDP). Findings indicate that a 1% increase in tertiary education leads to a 0.035% decrease in unemployment in the short run and a 0.130% decrease in the long run (both significant at the 1% level). Per capita GDP growth and inflation also reduce unemployment. At the same time, government consumption raises unemployment based on large-scale dynamic analysis in middle-income countries during the post-financial crisis era. The previous literature tends to focus on high-income and static environments. Tertiary education continues to play a key role in addressing unemployment and skills mismatches, according to this research. The authors recommend that greater effort should be directed toward investments in higher education in the context where skills are least aligned with labor market needs, as a big part of public expenditure to generate more employment opportunities.